The Gaze of Five Chinese Women in the 1980s : Golden Fingernails (金色的指甲, 1989) - Peng Qingyue; 장우진 (아시아영화연구, 2021)
As a Chinese feminist film born in 1989 when China begun to absorb the Western feminist film theory, the film Golden Fingernails 金色的指甲 tells the stories of five modern female citizens based on the reportage Ten Women 女十人谈. This paper is a systematic study of the female gaze in the film from the perspective of Laura Mulvey's article Visual Pleasure and Narrative Cinema published in 1975 and introduced to China in a Chinese-translated version in 1988. The female director openly challenged the male/active and female/passive viewing mechanisms of Hollywood mainstream movies mentioned in the article. This paper is more about criticizing the oppression of women by Chinese feudal doctrines through analyzing the ugly woman image of the protagonist and her erotic gaze towards the opposite gender. It analyzes the jealous gaze of the female character against the polygamy system. It criticizes the immorality of asking for chastity for women and setting double standards in the marriage for the rights of the male in the patriarchal society. It compares the ugly woman in the film with the famous image Dong Shi东施 to illustrate the awakening feminist consciousness of Chinese women in the new era.
Keywords: 1980년대 중국; 여성 응시; (1989); 로라 멀비; 못생긴 여성 이미지; China 1980s; female gaze; Golden Fingernails (金色的指甲; 1989); Laura Mulvey; the ugly woman image